Accelerated Fermentation of Pineapple Peel-Based Eco-Enzyme with Ganoderma lucidum: A Novel Bioconversion Strategy for Antidermatophytic - Hasna Ul Maritsa; Anggari Linda Destiana; Uni Baroroh Husnuddin; Putri Dwi Mulyani; Diah Tri Utami; Aris Abdul Rasid (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2026)
Pineapple peel waste, rich in lignocellulosic compounds and bioactive metabolites, remains underutilized despite its potential. Traditional eco-enzyme production from pineapple peels, molasses, and water (3:1:10 ratio) requires 90 days of spontaneous fermentation, limiting efficiency. This study investigates Ganoderma lucidum, a medicinal white-rot fungus, as a biocatalyst to accelerate fermentation and enhance antidermatophytic activity against Trichophyton rubrum. Fermentation substrates were prepared with or without G. lucidum mycelial plugs and monitored at 15 and 45 days for pH, aroma, color, and organoleptic changes. Eco-enzyme efficacy was assessed via agar well diffusion assays at concentrations of 20%, 40%, 60%, 80%, and 100%, measuring T. rubrum colony diameters.Results showed G. lucidum significantly hastened organic decomposition and secondary metabolite production. By day 45, inoculated samples reached pH 2.85 (vs. 3.2 in controls), exhibited faster aroma stabilization and darker coloration, and achieved complete inhibition (0.0 mm colony diameter) across all concentrations. At day 15, inhibition was already strong (0.7 mm vs. 90 mm in untreated controls). This approach reduces fermentation time by over 50%, yielding a potent antifungal agent from waste. It offers a sustainable bioconversion strategy for eco-enzyme production with therapeutic potential.